STRATEGI PENGALOKASIAN ASET DALAM RANGKA OPTIMALISASI PERTUMBUHAN KEKAYAAN PADA MASA TRANSISI BAPAK KUSHENDY - , Aulia Gema Fahmi ([Yogyakarta] : Universitas Gadjah Mada, 2012)
This thesis is a case study that discusses the management of wealth of Mr.Kushendy who has entered the transition period of 51 years of age. At this time the client has not maximize his retirement planning and future needs for children's education and marriage funds. Wealth management at this time focused on asset allocation in the form of physical assets, particularly in the form of land or house assets. Asset allocation that is done currently is less optimal for the growth of client wealth and high liquidity risk that the necessary reallocation also considers about planning for future of the client and his children. Wealth management is based on client tolerance towards risk in this thesis. The client has a moderate level of risk tolerance, so that the draft recommendation was made that the investment scenario is in accordance with the client's risk tolerance and age of client who have entered the transition stage. Therefore, two scenarios were made on investment planning, the capital of which came from asset sales. Scenario one is designed to have a lower return than scenario two. In scenario one, it would increase the wealth of client to be as much as Rp18.154.593.700, 00 and in scenario two, it will increase the wealth of the client into Rp18.481.152.100, 00. In terms of net cash flows, scenario two generate net cash flows greater than scenario one.